Biosynthetic pathways of the osmolytes N epsilon-acetyl-beta-lysine, beta-glutamine, and betaine in Methanohalophilus strain FDF1 suggested by nuclear magnetic resonance analyses. - Roberts, M F (1992)
Methanohalophilus strain FDF1 synthesizes beta-glutamine, betaine, and N epsilon-acetyl-beta-lysine as osmoprotective agents when the cells are grown in high external concentrations of NaCl. Nuclear magnetic resonance spectroscopic analyses of 13CH3OH-12CO2 label incorporation by the cells provide information on the biosynthetic pathways of these organic osmolytes. The labeling studies indicate that Methanohalophilus strain FDF1 produces glutamate and beta-glutamine via a partial oxidative Krebs pathway. 13C labeling of betaine is consistent with methylation of glycine generated from serine (via serine hydroxymethyltransferase). The labeling pattern for N epsilon-acetyl-beta-lysine is consistent with the synthesis of its precursor alpha-lysine occurring by the diaminopimelate pathway in these cells.